Brainstorm/J: Un framework para agentes inteligentes - Zunino, Alejandro (2002)
Intelligent agents and multi-agent systems (MAS) are one of the most rapidly developing areas of research of the last years. Agents offer new ways to analyze, design and implement software systems, improving, potentially, the ways in which software is modeled and then materialized by using a programming language